The Influence of Brand Image, Service Quality and Price Perception on Intervention to Repurchase Mulia Metal Gallery 24 With Customer Satisfaction as An Intervening Variable (Gallery 24 Regional Central Java) - Muhammad Tarmuji; Dendi Agung Gemilang (Garuda Prestasi Nusantara Consulting, 2023)
This study aims to determine and explain the influence of brand image, service quality and price perceptions on repurchase intention with customer satisfaction as the intervening variable. This research is a quantitative study with Galeri 24 customers in the Central Java region as the population. The sample of this research is 160 respondents from Gallery 24 customers in the Central Java Region with a non-probability sampling technique. The data sources for this research are primary and secondary data. The data analysis method uses SEM-PLS with SmartPLS version 3.2.0 software. (1) The results of the study show that brand image, service quality and price perceptions have a significant positive effect on customer satisfaction. (2) Customer satisfaction and price perceptions have a positive and significant impact on repurchase intention. (3) Brand Image and Service Quality have no direct effect on repurchase intention. (4) Customer satisfaction has a positive and significant effect in mediating brand image, service quality and price perceptions on repurchase intention Keywords: Brand Image, Service Quality, Perceived Price and Repurchase Intention